Technical-Tactical Actions That Lead to Winning in Male Taekwondo in Super-Elite Combats; [Acciones Técnico-Tácticas de Ganadores en Taekwondo Masculino Súper-Elite] - Aedo-Munoz, E (Didactic Asociation Andalucia, 2023)
A technical-tactical analysis in taekwondo matches pointed out crucial points to achieve maximum performance. This study compared the technical-tactical analysis by frequencies, absolute time and time ratio among male athletes who competed in the final taekwondo Grand Prix. For this, we applied a specific protocol, this study compared elements of technical and tactical interactions of male competitive matches. The main results showed that the technical-tactical actions, winners showed a higher frequency of attacks resulting in 1-point [3.0 (1.0; 5.3) vs. 6.5 (3.8; 10.0), p≥0.001]; in turn, losers showed a higher frequency of rear displacement [18.5 (13.5; 24.0) vs. 11.5 (6.8; 21.0); p=0.031]. There was a difference between the absolute time devoted to the variables Titchagui (p=0.037), Cover kicks (p=0.024), Punch (p=0.028), where losers had a higher frequency. In conclusion, winning athletes showed a higher efficiency in making attacks that result in 1 and 3 points; on the other hand, defeated athletes demonstrate more frequency regarding the use of techniques which are less effective in terms of scoring and move further back. © 2023 Didactic Asociation Andalucia. All rights reserved.